THE CONTENT ANALYSIS OF BAHASA INGGRIS TEXTBOOK USED IN THE FIRST CLASS OF SENIOR HIGHT SCHOOL 1 NAN SABARIS - Johari, Indra; Syaveny, Niza (TELL - US JOURNAL, 2022)
This research was based on varieties textbook circulating in learning. The method used in this research is descriptive research method, by analyzing the book "English" Semester 1 published by the Ministry of Education and Culture, English Language Book Revised 2017. The instrument used by the researcher was the Assessment rubric from the National Education Standards Agency Badan Standar Nasional Pendidikan (BSNP) and Documentation. The data were analyzed by using the conformity tabulation of the BSNP rubric and the range category in percentage form.The results of this study indicate that the total percentage obtained is 93.75% and is included in the Good category. This total percentage is obtained from the score on Material Completeness in 5 chapters getting a score of 4 or reaching 95% of the completeness of the material and 1 chapter getting a score of 1 or less than 95% of the completeness of the material. The in-depth score obtained in 5 chapters gets a score of 4 or 95% of the specified in-depth and 1 chapter gets a score of 1 or less than the specified 95% in-depth. The percentage assessment on the Social Function from Chapters 1-6 gets a score of 6 or reaches 95% of the social function provisions of the BSNP. The percentage value of Generic Structure here is 5 chapters getting a score of 4 or meeting 95% of the Generic Structure standards available in the BSNP rubric and 1 chapter getting a score of 1 or the achievement of Generic Structure is less than 95%, the percentage results from Linguistic Features in all the subjects studied are from the chapter 1-6 get a score of 4 or the percentage of achievement from Linguistic Features reaches 95%. The percentage achievement for Supporting Materials has 3 assessment points, namely Relevance, Development of Life Skills and Development of Diversity Insight. Here in chapters 1-6 each gets a score of 4 or reaches 95% of each category. So based on the results that have been examined in this study, the percentage category of achievement of this book is included in the Good category.